2012
DOI: 10.26719/2012.18.8.892
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and pragmatism in promoting health: an experience of synergy between health and religion in the Islamic Republic of Iran

Abstract: In the Islamic Republic of Iran, religion has traditionally played a central role in the lives of the people. Following the Islamic Revolution in 1979, it has also become integral to the country's governance. Since the Revolution, an exceptional synergy has arisen between the domain of religion and the health sector in the development of family planning policies, which have resulted in dramatic changes in population growth and fertility: the population growth rate decreased from 3.9% (1986) to 1.2% (2000) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…On the other hand, statistics showed that the highest level of implementation was related to personal hygiene items, such as Wearing a mask when in public, handwashing, and covering mouse while sneezing or coughing, which is contrary to the results of other countries such as Greece (Kamenidou, Stavrianea, & Liava, 2020) or Japan (Machida et al, 2020a;Machida et al, 2020b) and can be attributed to existing cultural differences. Because in the Islamic Republic of Iran, personal health education and the need to observe it have been emphasized from the most elementary courses based on teachings of Islam and have affected Iranians' health customs (Adams & Manenti, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, statistics showed that the highest level of implementation was related to personal hygiene items, such as Wearing a mask when in public, handwashing, and covering mouse while sneezing or coughing, which is contrary to the results of other countries such as Greece (Kamenidou, Stavrianea, & Liava, 2020) or Japan (Machida et al, 2020a;Machida et al, 2020b) and can be attributed to existing cultural differences. Because in the Islamic Republic of Iran, personal health education and the need to observe it have been emphasized from the most elementary courses based on teachings of Islam and have affected Iranians' health customs (Adams & Manenti, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Between the 2005 and 2010 time period, the healthcare system of Iran was well established and innovative, especially in the case of birth control promotion (40,143,147). After the 1979 Islamic Revolution, the cooperation between religious authorities and health officials resulted in the development of a comprehensive family planning education and promotion programme which provided free contraceptive methods and health guidance by trained staff starting in 1988 (147,152,153). Healthcare personnel promote the use of birth control methods to all adult married couples who visit healthcare facilities, which also includes Afghan migrants (147).…”
Section: Iranmentioning
confidence: 99%
“…Healthcare personnel promote the use of birth control methods to all adult married couples who visit healthcare facilities, which also includes Afghan migrants (147). The implementation of the birth control programme in Iran was highly successful, resulting in a decrease in the fertility rate from 6.8% in 1984 to 2.1% in 2000 and an increase in the use of birth control methods from 49% in 1989 to 73.8% in 2006 (152,153). Recently, however, the future of Iran's progressive birth control programme has been uncertain, as Ayatollah Ali Khamenei criticised the programme as too Western and stressed the objective of boosting the Iranian population.…”
Section: Iranmentioning
confidence: 99%
See 2 more Smart Citations